Mean queue time study for the Lu-Kumar network - Nyan, Soe Lynn (2014)
Manufacturing system, communication network, silicon wafer manufacturing plant, internet service provider domain and freeway system are usually modelled with multi-class queuing network. The aim of this project is to deeply understand the nature of the Lu-Kumar network. The queue time of the Lu-Kumar network is hard to predict due to the mutual blocking of virtual stations in the network.